On Output Feedback Stabilization of Time-Varying Decomposable Systems with Switching Topology and Delay. Issue 2 (2020) - Zakwan, Muhammad; Ahmed, Saeed; Bajcinca, Naim
Abstract: This paper presents a new method for dynamic output feedback stabilizing controller design for decomposable systems with switching topology and delay. Our approach consists of two steps. In the first step, we model the decomposable systems with switching topology as equivalent LPV systems with a piecewise constant parameter. In the second step, we design stabilizing output feedbacks for these LPV systems in the presence of a time-varying output delay using a trajectory-based stability analysis approach. We do not impose any constraint on the delay derivative. Finally, we illustrate our approach by applying it to the consensus problem of non-holonomic agents.